Algae as Biological Indicators of Water Pollution - Dobrescu, Codruța Mihaela; Turtureanu, Anca; Dorobat, Leonard Magdalin (Journal of Danubian Studies and Research, 2023)
Water pollution is a major environmental problem that has existed for decades, perhaps even longer, and is becoming more and more serious, necessitating the need for efficient, accurate and if possible inexpensive methods of monitoring and evaluating its impact on aquatic ecosystems. Algae, as photosynthetic organisms, have gained considerable attention as reliable biological indicators of water pollution due to their high sensitivity to environmental changes and their wide distribution in all categories of aquatic habitats. The unique characteristics of algae, a wide variety of species and their ubiquity in different types of water make them suitable candidates for such indicators. Algae respond rapidly to changes in water chemistry, temperature and nutrient levels, making them sensitive to various types of pollution including heavy metal pollution, organic pollutants and excess nutrients, various methods and techniques can be used to measure and assess algae responses to water. Pollution, determining both quantitatively and qualitatively the level of pollution. These techniques range from traditional microscopy-based identification and enumeration to more advanced molecular methods such as DNA barcoding and high-throughput sequencing. In addition, the use of bioindicators derived from algal communities, such as algal and biotic indices, is discussed as a valuable tool in water quality assessment. The potential of algae to detect and monitor pollution events, assess the ecological health of water bodies, and evaluate the effectiveness of pollution control measures is high and incompletely exploited in Romania and beyond. Factors such as natural variability, species-specific responses, and the need for standardized protocols, emphasizing the importance of considering these factors when interpreting algal data, are crucial issues and still need to be well established. Continuing research in this field is crucial for perfecting the use of algae as indicators and developing standardized protocols at the international level (EU and not only) for their application in water quality assessment.